Economic Analysis of Libyan Imports for the Most Important Vegetable Oils Using Almost Ideal Demand System During the Period (1990-2013). - محمد سالم على موسى و محمد بلعيد على (Journal of Pure & Applied Sciences, 2018)
The main aims of this study were to estimate the Almost Ideal Demand System (AIDS) for the Libyan imports of the most important vegetable oils (corn oil, soybean oil, sunflower oil) during the period (1990-2013), as well as to evaluate the imports development and per capita of these oils during same period. The methodology of this study based on the use of both descriptive and econometric methods analysis approach to achieving its objectives. The most important results obtained were that, Imports of the three oils (corn oil, soybean oil, sunflower oil) have increased with an annual growth rate of 1.7%, 5.2% and 9.1%, respectively during the period of study. The statistical estimation obtained from the Almost Ideal Demand System on the imports of these oils showed an inverse relationship between the prices of soybean oil and corn oil and sunflower oil and the percentage of expenditure on it. The correlation between soybean oil and oil corn and sunflower oil based on intermittent demand flexibilities, that means the soybean oil, corn oil and sunflower oil are essential commodities for the Libyan consumer.